Disruption and Rerouting in Supply Chain Networks - Birge, John R.; Capponi, Agostino; Chen, Peng-Chu (Operations Research, 2023)
The recent coronavirus disease 2019 pandemic has shown that shortages and supply chain disruptions can have catastrophic effects on the real economy. These observations bring about reflections and first-order questions. How can we design supply chain networks that are robust and resilient to demand and supply shocks? Can we quantify the indirect effects caused by buyers’ and suppliers’ defaults in the network? Is it always cost effective to steer the system toward higher buyers’ and suppliers’ diversification? In the paper “Disruption and Rerouting in Supply Chain Networks,” Birge et al. argue that in highly capitalized networks, diversifying demand and supply across a larger number of counterparties may result in a more fragile network. Single-sourcing strategies are optimal for a firm only if the firm’s supplier default probability is low, but they perform worse than multiple-sourcing strategies otherwise.